Wybrane zagadnienia edukacji osób z niepełnosprawnością intelektualną w czasie pandemii COVID-19 - Więcek, Sara (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The article presents a pandemic situation in Poland, specifically the education of people with intellectual disabilities. It contains regulations by law and conclusions from research by Polish Economic Institute. The main aim is a comparison of statement of work rules with people with disability and offers possibilities by remote education. The analysis presents both advantages and disadvantages this solution. Despite the quantitative disproportion, it is important, that decision about close special facilities was necessary intervention. This resolution intended to save not only the healthy, but also the live.